IMPLEMENTASI MANAJEMEN STRATEGIS TERHADAP MUTU PENDIDIKAN DI MADRASAH ALIYAH PERGIS CAMPALAGIAN KAB. POLEWALI MANDAR - Hamriani Sari; Husain As; Nawir Rahman (Melati Institute, 2022)
This study aims to determine the description of strategic management and the quality of education in Madrasah Aliyah Pergis Campalagian and determine the implementation of strategic management on the quality of education in Madrasah Aliyah Perus Campalagian Kab. Polewali Mandar. This type of research is a qualitative research. The instruments used to collect data are interviews and documentation and then analyzed using reduction analysis, display and analysis stages of verification and conclusion drawing. The results of this study illustrate that the implementation of strategic management at Madrasah Aliyah Pergis Campalagian is going well. However, this needs to be improved, especially in the aspect of strategy formulation and implementation. Meanwhile, the quality of education in Madrasah Aliyah seen from the input, process and output requires management activities, especially in the input and educational process aspects. The implementation of strategic management on the quality of education must be supported by the leadership of qualified principals, so as to produce the right decisions.